2020
DOI: 10.1186/s13052-020-00932-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of family accommodation and parental psychological distress in a sample of children and adolescents with obsessive-compulsive disorder aged 8-17 years old

Abstract: Background Family Accommodation (FA) refers to the involvement of family members (especially parents) in the compulsive behaviors of children and adolescents with Obsessive-Compulsive Disorder (e.g. modifying family routines or facilitating avoidance of obsessive-compulsive triggers). Many studies have examined the high prevalence of FA in this clinical population; however, less is known about its clinical significance and relationship to the individual psychological distress of parents. In our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…When cognitive behavioral therapy that is designed to decrease anxiety symptoms is applied to adolescents, the intervention can also ameliorate depressive symptoms (e.g., Ishikawa et al, 2019). Some studies have also shown that adolescents with high accommodation tend to have greater depressive symptoms than those with low accommodation (e.g., Kobayashi et al, 2017; Pontillo et al, 2020).…”
Section: The Current Researchmentioning
confidence: 99%
“…When cognitive behavioral therapy that is designed to decrease anxiety symptoms is applied to adolescents, the intervention can also ameliorate depressive symptoms (e.g., Ishikawa et al, 2019). Some studies have also shown that adolescents with high accommodation tend to have greater depressive symptoms than those with low accommodation (e.g., Kobayashi et al, 2017; Pontillo et al, 2020).…”
Section: The Current Researchmentioning
confidence: 99%
“…Additionally, the role of Parental Psychological Distress (PPD) in families of children and adolescents with ASD and AD should not be underestimated. PPD is defined as family members’ distress, resulting in high levels of family conflict and increased expressed emotions, defined as criticism, hostility, and emotional over-involvement [ 10 , 11 ]. Parents of children with ASD have higher parental stress levels and lower quality of life than parents of normotypical children [ 12 , 13 , 14 , 15 ], similar to parents with disabled children (e.g., Down syndrome, cerebral palsy, and intellectual disability) [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mainly, high rates of accommodation among families of children with OCD suggest that up to 60-96% of relatives modify their family routines and even perform the child's rituals (22,(26)(27)(28)(29)(30)(31)(32). Second, the absence of or little introspection of minors can hinder involvement in treatment; also, the parents can participate as co-therapists and carry out exposure tasks at home, allowing us to come closer to ideal treatment as this contributes both to generalizing and maintaining achievements, and so on (5,14,(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%